If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 3x + 5 = 6x + 7 + -6x Reorder the terms: 2 + 5 + 3x = 6x + 7 + -6x Combine like terms: 2 + 5 = 7 7 + 3x = 6x + 7 + -6x Reorder the terms: 7 + 3x = 7 + 6x + -6x Combine like terms: 6x + -6x = 0 7 + 3x = 7 + 0 7 + 3x = 7 Add '-7' to each side of the equation. 7 + -7 + 3x = 7 + -7 Combine like terms: 7 + -7 = 0 0 + 3x = 7 + -7 3x = 7 + -7 Combine like terms: 7 + -7 = 0 3x = 0 Solving 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '3'. x = 0 Simplifying x = 0
| 9a^2+30a+25/6a^2+a-15 | | 2-2(3x-4)=8-2(5+x) | | 8=p-11 | | a-5=-1+3a | | 3x+5-5=-2x-10 | | -24=-7+x | | 8=14-n | | -10=3x+8+4(x-1) | | 5(2x-1)=3(3x-1) | | 5x-5=3x+10 | | lnx+12x=3.916 | | 3(x+1)=1 | | 3x-8-5x+2=-12 | | 5x-6x-3=0 | | 18/21/4 | | 3x-5y+8=0 | | -5=-z-3 | | 6/7/(-1/3) | | a=b+2b+b-101 | | yu=89 | | m/3=-6 | | 3*a=5*a*8 | | 7.50x/100=617.05 | | x-7.50x/100=617.05 | | 12*17/6 | | 23+x=16 | | 12*7/6 | | f(x)=(x+2)(x-3)-6 | | 5*3/5 | | 4x-8y+12xy=101 | | 4xy+6=8xy-12 | | x+2x+3x+4x+5x+6x+7x+8x+9x+10x+11x+12x+13x+14x+15x+16x+17x+18x+19x+20x+21x+22x+23x+24x+25x+26x+27x+28x+29x+30x=1 |